2014
DOI: 10.1093/qjmed/hcu095
|View full text |Cite
|
Sign up to set email alerts
|

Autologous stem cell transplantation in severe treatment-resistant Crohn's disease: long-term follow-up of UK patients treated on compassionate basis

Abstract: Long-term follow-up supports the safety and feasibility of ASCT as a means of achieving short-term control of severe CD whilst potentially re-sensitizing the disease to medical therapy and reducing requirements for surgery and TPN. Given the inevitability of relapse, pre-emptive salvage and/or maintenance treatments post-ASCT should be the focus of future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…6 There has been considerable interest in case reports that autologous haematopoietic stem cell transplantation (HSCT) can induce sustained disease remission in such patients. [7][8][9][10][11][12][13] The ASTIC trial compared outcome at one year in 23 patients with refractory CD after autologous HSCT to 22 undergoing stem cell mobilisation alone. 14 This was a negative trial and few patients in either arm achieved the ambitious primary endpoint of clinical remission off therapy for 3 months with no endoscopic or radiological evidence of intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…6 There has been considerable interest in case reports that autologous haematopoietic stem cell transplantation (HSCT) can induce sustained disease remission in such patients. [7][8][9][10][11][12][13] The ASTIC trial compared outcome at one year in 23 patients with refractory CD after autologous HSCT to 22 undergoing stem cell mobilisation alone. 14 This was a negative trial and few patients in either arm achieved the ambitious primary endpoint of clinical remission off therapy for 3 months with no endoscopic or radiological evidence of intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Through a Phase I/II study of 12 patients, Hasselblach et al also demonstrated that HSCT can induce remission in refractory Crohn disease; however 78% relapsed after a mean of 10 months. Similarly Snowden et al conducted a retrospective evaluation on six patients with severe treatment resistant Crohn disease demonstrating 83% obtaining remission at 3 months and again median time to next treatment being 10 months. In both studies there was a pattern of patients coming off total parenteral nutrition and reducing the need for surgery despite recurrence of disease.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a total of 138 cases have been described (Table ) who were rescued from an invalidating condition by this therapeutic strategy despite the withdrawal of drugs in most of them . However, the lack of objective data on mucosal healing in several cases may have resulted in an overestimation of the success rate.…”
Section: Cellular Therapies In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Altogether, these studies highlight that the benefit for refractory patients treated with autologous HSC transplantation is only slightly superior to the best available medical care at 1 year, thus their exposure to increased toxicity and mortality risk seems unacceptable . Finally, the rate of clinical relapse鈥恌ree survival, defined as the percentage of patients who do not need to restart medical therapy, decreases progressively over time . In this regard, a still unsolved matter regards whether the reappearance of symptoms should be considered a relapse due to residual pathogenic T cells or a new鈥恛nset of the same disease due to the strong influence of environmental factors in converting genotypic predisposition into frank disease.…”
Section: Cellular Therapies In Inflammatory Bowel Diseasementioning
confidence: 99%